Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1089/apc.2006.0112
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Facilitators to Adolescent HIV Testing

Abstract: This study examined the barriers and facilitators of HIV counseling, testing, and referral service (HIV CTR) acceptance among 278 youth aged 12-24 years old. Participants completed a questionnaire before health education sessions with trained counselors. Information was collected on individual characteristics, HIV testing acceptance, risk behaviors, reasons for having never been tested, and what would make it easier to get tested for HIV. Ninety percent of the respondents were minority and 52% were female with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
100
3
15

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(128 citation statements)
references
References 29 publications
10
100
3
15
Order By: Relevance
“…Furthermore, low perception of risk has been cited as a reason for HIV testing refusal among adolescents. 33 Thus, our finding that testing acceptance among pediatric patients increased with age is logical, because HIV risk behavior and risk perception are also likely to increase with age.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Furthermore, low perception of risk has been cited as a reason for HIV testing refusal among adolescents. 33 Thus, our finding that testing acceptance among pediatric patients increased with age is logical, because HIV risk behavior and risk perception are also likely to increase with age.…”
Section: Discussionmentioning
confidence: 94%
“…16,34 In addition to low perception of risk, never having been offered a test has been identified as a reason for not having an HIV test among adolescents. 33 Moreover, ED-based testing programs with extensive counseling and consent procedures seem to reduce the percentage of adolescents tested. 34 In 2006, persons age 13 to 29 years accounted for the largest number of new HIV infections (34%).…”
Section: Discussionmentioning
confidence: 99%
“…National data indicate that approximately 87 % of people are HIV tested at medical facilities (e.g., 41 % at sexuality transmitted infection or community health clinics, 14 % at correctional medical facilities), while only 7 % are tested at community-based organizations and 6 % at substance abuse treatment centers [8]. In general, there are significant barriers to clinic-based HIV testing for adolescents, including inconvenience (e.g., time, location, transportation), confidentiality concerns, and fears of being socially stigmatized if observed attending a testing site [9][10][11][12][13][14]. HIV selfimplemented testing (SIT) offers a viable option for addressing these problems by increasing privacy and convenience [e.g., see 15].…”
Section: Overviewmentioning
confidence: 99%
“…The use of an oral fluid testing device that measures HIV antibody in mucosal transudate is well accepted by youth and is used in many outreach settings. 16 In addition, several point-of-care rapid HIV-1 antibody tests provide results in minutes to hours. 29 These tests have sensitivity and specificity rates similar to those for standard EIA.…”
Section: Testing For Hivmentioning
confidence: 99%
“…Adolescents also cite concerns about confidentiality, access to testing, and invasive blood procedures as barriers to testing. 16 A 2005 American Academy of Pediatrics survey revealed that nearly 50% of pediatricians recommend that all sexually active youth be screened for STIs; however, only 28% of them recommend that all adolescents be tested for HIV. 17 In light of the increasing numbers of people with HIV/AIDS and missed opportunities for HIV testing, the Centers for Disease Control and Prevention (CDC) recommends universal and routine HIV screening rather than targeted testing.…”
mentioning
confidence: 99%